A grammar of Old Assyrian - Kouwenberg, Bert (Handbook of Oriental Studies, 2017)
A Grammar of Old Assyrian describes the language contained in a very large corpus of cuneiform tablets mainly found in Anatolia in the middle of Turkey and dating to ca 1900-1700 BC. These tablets come from the archives of a community of Assyrian merchants who conducted a long-distance trade between Assyria and Anatolia and eventually settled in Anatolia. Alongside Babylonian, Assyrian is one of the main branches of Akkadian, the Semitic language spoken in Mesopotamia (roughly present-day Iraq) in the third, second and first millennium BC, and Old Assyrian is its oldest attested stage. Old Assyrian is also one of the oldest and largest corpora of texts in any Semitic language. "Kouwenberg has managed to describe and discuss the corpus in a structural and comprehensive manner. His grammar will therefore prove to be a useful source of information for decades